The Impact of Terrorism on the Tourism Sector of Lithuania - Arvydas Survila; Edvinas Mikėnas; Brigita Žuromskaitė (Montenegrin Journal of Economics)
Practically every day there are terrorist attacks executed somewhere. For this reason, the need to reveal the impact of terrorism on tourism sector of Lithuania and how well it is ready for this challenge occurs. The analysis of scientific literature and secondary data was used as well as two surveys (qualitative and quantitative) were carried out. Since the possibility of a terrorist attack in Lithuania is trivial, the research focuses on the Lithuanian outbound tourism sector. The survey of interaction between terrorism and tourism and impact of terrorism to tourism in different countries is provided. It is worth emphasising that tourists become the victims of not only preplanned but also of individual terrorist attacks. Events of recent several years have caused the emergence of the terrorist tourism, when people with radical attitudes travel to, e.g., Syria. Despite the various attacks and subsequent dips in tourism the world of travel and hospitality has entered a new era of growth and transformation. The purpose of the research was to identify how Lithuanian tourists and experts perceive dangers and whether this affect their choice of trips and what measures can reduce the impact of terrorist attacks on tourism. Both the Lithuanian tourists and experts understand that the threat from terrorism has been growing, nevertheless the comparison with other surveys can lead to the statement that there is a specific tourist market in Lithuania which is characteristic of courage, inflexibility in terms of price and poor perception of possible threats.